2021
DOI: 10.22541/au.161193241.11465772/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate variability and drought modulate the role of structural refuges for arthropods: a global experiment

Abstract: Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to drought, high temperatures and climate variability might persist in microclimatic refuges, such as leaf shelters built by arthropods. We conducted a distributed experiment across an 11,790 km latitudinal gradient to explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation and underlying climate. Our analyses revealed leaf shelters to be key fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Joos et al (1988), Alonso (1997), and Yule and Burns (2017) show that higher temperatures inside shelters positively affect caterpillar growth rate. In a replicated experiment using experimental leaf rolls conducted at 52 sites across the globe, Romero et al (2022) demonstrated that the use of these leaf rolls by herbivores was greater in locations with more arthropod predators, and decreased as temperature increased among locations. Together these results suggest both natural enemies and abiotic factors influence formation and colonisation of leaf ties, and their possible use as a food source.…”
Section: Discussionmentioning
confidence: 99%
“…Joos et al (1988), Alonso (1997), and Yule and Burns (2017) show that higher temperatures inside shelters positively affect caterpillar growth rate. In a replicated experiment using experimental leaf rolls conducted at 52 sites across the globe, Romero et al (2022) demonstrated that the use of these leaf rolls by herbivores was greater in locations with more arthropod predators, and decreased as temperature increased among locations. Together these results suggest both natural enemies and abiotic factors influence formation and colonisation of leaf ties, and their possible use as a food source.…”
Section: Discussionmentioning
confidence: 99%